Metode Pembelajaran Kolaboratif Dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam : Studi Kasus Smp Negeri 3 Lima Puluh - Nizar, Muhammad Alang Khairun (Community Service Progress, 2023)
The problem of this research is how to use collaborative learning methods in improving the learning outcomes of Islamic Religious Education in SMP Negeri 3 Lima Puluh? And what are the obstacles in using collaborative learning methods at SMP Negeri 3 Lima Puluh? This research is a type of qualitative research. The type of research whose findings are not obtained through statistical procedures or other forms of calculation and aims to reveal the symptoms holistically-contextually through the collection of data from natural settings by utilizing the researcher as a key instrument. The results of this thesis, the use of collaborative learning models has been used in SMP Negeri 3 Lima Puluh since the exit of the new curriculum, namely the 2013 curriculum. By using collaborative learning methods, a teacher of Islamic Religious Education is expected to be more able to guide, motivate students of SMP Negeri 3 Lima So many students concentrate more on following the path during the teaching and learning process in class. The process of learning determines learning achievement. Every student has a difference in learning achievement. Some tend to be high, others tend to be low. Learning achievements of Islamic Religious Education achieved by students in SMP Negeri 3 Lima Puluh are very good results thanks to the efforts of teachers to maximize their learning.